ANALISIS RENDAHNYA MINAT BELAJAR PESERTA DIDIK BROKEN HOME KELAS VIII SMP NEGERI 1 SIMPANG HULU - Agustina Merlin; Indri Astuti; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe purpose of the study was to describe the learning interest of broken home student at Simpang Hulu Junior High School. The research method used is qualitative through a descriptive approach. The role of the researcher in this study is as a research observer. The research location was conducted at Simpang Hulu Junior High School. The research subject consisted of grade eight subject. Data collection techniques used, interviews, and documentation. Interview guide data collection tool and documentation recording divice. Data analysis with reduction, data presentation, conclusion drawing. Techniques for checking the validity of source triangulation data. The factors causing the students’ low interest in learning are (1) family, (2) subject, and (3) facilities and infrastructure. The impact of low interest in learning is, (1) decreased academic achievement, (2) difficulty understanding science, (3) neglect of assignment. The efforts made by counseling guidance teachers are provide individual counseling services to the students concerned.Keywords: Broken Home, Interest in Learning, Individual Counseling